2008
DOI: 10.1111/j.1463-1318.2007.01413.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for acute and chronic pouchitis following restorative proctocolectomy for ulcerative colitis

Abstract: Pouchitis is a heterogeneous disease which tends to occur early after restoration of gastrointestinal continuity. Patients with backwash ileitis and/or PSC are at considerable risk of developing chronic pouchitis. The strong association between backwash ileitis, PSC and chronic pouchitis suggests a common link in their pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
63
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 45 publications
12
63
2
Order By: Relevance
“…The incidence within the first 12 months after ileostomy closure was as high as 40% according to a clinical trial [16]. In patients with pouchitis, 70% had the initial episode during the first 12 months after ileostomy closure [17], although late-onset pouchitis can occur years afterwards. …”
Section: Incidence and Prevalencementioning
confidence: 99%
“…The incidence within the first 12 months after ileostomy closure was as high as 40% according to a clinical trial [16]. In patients with pouchitis, 70% had the initial episode during the first 12 months after ileostomy closure [17], although late-onset pouchitis can occur years afterwards. …”
Section: Incidence and Prevalencementioning
confidence: 99%
“…The reported cumulative frequencies of developing pouchitis 10-11 years after IPAA are 23-46%, and approximately 50% of patients with UC who undergo IPAA develop at least one episode of pouchitis [2,3,4,5]. Approximately 20-45% of patients diagnosed with pouchitis have chronic inflammation that requires long-term courses of antibiotics and other medications [2,6,7,8]. …”
Section: Introductionmentioning
confidence: 99%
“…[2,5,8,9,10,11,12,13,14,15,16]. Some of these studies evaluated predictive factors for the development of both acute and chronic pouchitis in combination [2,9,11], but other studies focused on predictive factors for acute and chronic pouchitis individually [8,10,12,13,14,15,17,18]. It was suggested that acute and chronic pouchitis may have different risk factors and pathogeneses [8,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…(male impotence) and Abdelrazeq et al 137 (chronic pouchitis). Perioperative and post-operative mortality risks were estimated using a study reported by Roberts et al 138 taking account of background mortality rates.…”
mentioning
confidence: 99%
“…Transition probabilities: post-surgery complications and surgery related-mortality Transition complications rates estimated from Swenson et al 115 Chronic complication rates estimated using studies by Johnson et al 135 (fertility), Kruasz andDuek 136 (male impotence) and Abdelrazeq et al 137 (chronic pouchitis). Perioperative and post-operative mortality risks were estimated using a study reported by Roberts et al…”
mentioning
confidence: 99%